Pengaruh Model Snowball Throwing terhadap Hasil Belajar Siswa Kelas IV SD Negeri Bandung 1 Jombang - Ardianti, Putri Dwi; Nuruddin, Muhammad (Jurnal Simki Postgraduate, 2025)
The purpose of this research is to determine whether or not the snowball throwing approach improved fourth graders' understanding of big whole numbers at SD Negeri Bandung 1 Diwek Jombang. Innovative tactics are required since conventional approaches are seen as less successful. The purpose of this research is to evaluate the model's efficacy in enhancing students' comprehension and learning outcomes through collaborative efforts. In order to determine if the snowball throwing model improved the academic performance of fourth graders at SD Negeri Bandung 1, this research employed an experimental approach based on a one-group pretest-posttest design. We used SPSS paired sample t-tests to examine the data we gathered from the exams and the paperwork. How well the model works to enhance pupils' knowledge is determined by the study's findings. The findings demonstrated that the snowball tossing approach significantly impacted the learning outcomes for the children. A post-test average of 86.92 rose from a pre-test average of 66.46. This model's efficacy was demonstrated by the t-test, which had a significance level of 0.000 < 0.05. We advocate snowball tossing as a learning activity because it enhances students' engagement, comprehension, and social skills. The results of this study demonstrate that the snowball tossing model improves pupils' academic performance. Students still had a poor grasp of the material prior to applying this methodology. Students' involvement and comprehension skyrocketed after its implementation. Analytical findings show a discernible change between pre- and post-implementation of this learning paradigm.